A randomised, double-blind, placebo-controlled, 24-week, phase II, proof-of-concept study of romilkimab (SAR156597) in early diffuse cutaneous systemic sclerosis. Issue 12 (22nd September 2020) - Allanore, Yannick; Wung, Peter; Soubrane, Christina; Esperet, Corinne; Marrache, Frederic; Bejuit, Raphael; Lahmar, Amel; Khanna, Dinesh; Denton, Christopher P
Abstract : Objectives: Recent advances in systemic sclerosis (SSc) show that it involves a T-helper type-2-oriented immune response with interleukin (IL)-4 and IL-13. Romilkimab is an engineered, humanised, bispecific immunoglobulin-G4 antibody that binds and neutralises IL-4/IL-13 making it ideal for exploration in fibrosis. Methods: Patients aged ≥18 years diagnosed with diffuse cutaneous SSc (dcSSc), and with or without immunosuppressive background therapy, were randomised (1:1) to subcutaneous romilkimab 200 mg or placebo one time per week for 24 weeks in this double-blind, proof-of-concept, phase II study. The primary endpoint was change in modified Rodnan skin score (mRSS) from baseline to week 24. Results: Ninety-seven patients were randomised to romilkimab (n=48) or placebo (n=49) for 24 weeks. Least-squares mean (SE) change in mRSS was –4.76 (0.86) for romilkimab versus –2.45 (0.85) for placebo yielding a mean (SE) (90% CI) difference of –2.31 (1.21) (–4.32 to –0.31; p=0.0291, one-sided). Treatment-emergent AEs were balanced between placebo (n=41; 84%) and romilkimab (n=40; 80%). Most were mild-to-moderate and discontinuations were low (three overall). There were two deaths (one scleroderma renal crisis (romilkimab) and one cardiomyopathy (placebo)), neither were considered treatment related. Two patients in the placebo group had a cardiovascular treatment-emergent SAE (one cardiac failure, one cardiomyopathy), but there were no cardiac safety signals with romilkimab. Conclusion: This study demonstrated significant effects on skin changes with romilkimab in early dcSSc that require confirmation with a longer and more comprehensive phase III study to determine clinical relevance. Trial registration number: NCT02921971 .